Reassessing Organizational Competence as a Mediator between Service Quality and Customer Satisfaction: An Integrated SERVQUAL-Resource-based View Study of Amanah Ikhtiar Malaysia - Zainudin, Wan Nur Rahini Aznie Binti; Abdullah, W. Muhammad Zainuddin Wan; Mahussin, Norlida Binti; Zakaria, Farah Alia Binti (International Review of Management and Marketing, 2026)
The primary microfinance institution in the country, Amanah Ikhtiar Malaysia (AIM), is used as the case environment in this study to re-examine the presumed mediating function of organisational competency in the relationship between service quality and customer satisfaction. It examines whether internal capabilities like staff knowledge, operational effectiveness, and community outreach can mitigate the effects of service quality dimensions like tangibles, responsiveness, reliability, empathy, and assurance. It does this by incorporating the SERVQUAL framework and drawing on the Resource-Based View (RBV) theory. The research pursued four objectives: to investigate how service quality affects organisational competence, how organisational competence affects customer satisfaction, to assess whether organisational competence mediates this relationship, and whether service quality directly affects satisfaction. Using descriptive statistics and Ordered Probit Regression to analyse responses from 400 AIM clients, the study concludes that organisational competency does not significantly mediate the findings. Instead, service quality dimensions directly and significantly influence customer satisfaction. The significance of frontline service performance in promoting customer satisfaction and sustained involvement in microfinance is underscored by these findings.